KEBIJAKAN BAITUL MAL KABUPATEN PIDIE DALAM PEMBERDAYAAN EKONOMI PEDAGANG KECIL KOTA SIGLI - Syukri Syukri; Anwar Anwar (Jurnal Sains Riset, 2022)
Indonesian society which is dominated by people who with low education and lack of capital, make the choice for not much economic activity. For those who have entered working age, one type of work that can be done is to work or create jobs in the small business sector besides not requiring a lot of capital. Indonesia is very big. The role of micro, small and medium enterprises (MSMEs) turned out to be constrained by several things, including problems with capital. This is where Baitul Mal, Pidie Regency, with its economic empowerment program is expected to be an ideal solution for empowering small businesses, especially small traders in Pidie Regency. Therefore, this study wants to examine how the form of economic empowerment policy carried out by Baitul Mal in Pidie Regency is for small traders in Pidie Regency. The methodology used in this research is qualitative research. The process of this research is field research. Data collection was done by interview, observation and documentation. The results of this study indicate that Baitul Mal of Pidie Regency in distributing business capital assistance to small traders in Pidie Regency in the form of productive infaq into two forms of assistance, namely: cash assistance, in-kind assistance. As for the impact of economic empowerment from productive infaq that has been given by Baitul Mal, Pidie Regency to small swords, although it can help a little in developing their business. However, the little sword was not yet fully empowered.Keywords: Policy, Empowerment, Economy